ANALISIS KESESUAIAN LAHAN TANAMAN AGROFORESTRY DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT - Yamani, Ahmad; Rudy, Gusti Seransyah; Agustina R., Arfa; Radam, Rosidah R. (Jurnal Hutan Tropis, 2025)
The failure of forest and land rehabilitation activities has often been attributed to fires; however, this is not always the case. It may also be due to the recommended plant species being unsuitable for the habitat or lacking a scientific basis. To ensure the success of forest and land rehabilitation activities and achieve their goals, the paradigm must shift. Specifically, the selection or recommendation of plant species should align with the characteristics of the land and involve local communities, as such initiatives often fail without their participation. For this reason, an agroforestry system—rehabilitating forest areas by planting forestry and agricultural crops with local farmers—needs to be implemented. This study aims to analyze the land suitability classes for Candlenut (Aleurites moluccana WILLD) and Corn (Zea mays) as agroforestry crops in the Special Purpose Forest Area (KHDTK) of Lambung Mangkurat University. The significance of this research lies in providing solutions to prevent forest and land fires while addressing critical land issues in KHDTK ULM. In principle, land suitability classification is conducted by integrating the plant's growth requirements with the land's characteristics. Hence, this classification is often referred to as the "matching method." The research results indicate that, for candlenut plants, all observed land units fall into the "moderately suitable" actual land suitability class, limited by base saturation factors (S2nr), except for UL3, which falls under the "marginally suitable" class, also limited by base saturation (S3nr). In contrast, UL4 is classified as "highly suitable" (S1). If improvements are made, all observed land units could potentially be classified as "highly suitable" (S1), except for UL3, which would remain "moderately suitable" due to base saturation limitations (S2nr). For corn plants, land units UL1, UL2, and UL6 are classified as "moderately suitable," limited by temperature and base saturation factors (S2tc,nr). UL3 falls under the "marginally suitable" class, limited by temperature and base saturation (S3tc,nr), while UL5 is classified as "marginally suitable," limited by texture (S3rc). UL4, meanwhile, is "moderately suitable" with a temperature limitation (S2tc). With improvements, the potential land suitability for UL1, UL2, and UL4 would be "moderately suitable," limited by temperature (S2tc), while UL3 and UL5 would remain in the "marginally suitable" category, limited by texture (S3rc).